Unveiling Indonesian EFL students’ learning pathways: Experiences, challenges, and growth through student-created digital content for public speaking beyond the podium - Endang Susilowati; Etika Dewi Kusumaningtyas; Eka Fanti Sulistiyaningsih (EduLite: Journal of English Education, Literature and Culture, 2026)
The integration of digital media into language learning has expanded opportunities for EFL learners to practice speaking in more authentic, creative and self-directed ways, particularly through student-created digital content (SCDC) that enables learners to produce and share their own speaking performances. Public speaking remains a persistent challenge for Indonesian EFL college students, who often experience anxiety, limited exposure, and traditional instruction that restricts authentic speaking practice. This study explores the learning pathways of Indonesian EFL college students by examining their experiences, challenges, and growth while creating digital speaking content for public speaking practice. This study employed a qualitative case study design, involving nine English education students enrolled in a semester-long public speaking course. Data were collected through semi-structured interviews and reflective journals, analyzed using Braun and Clarke’s (2017) thematic analysis framework, grounded in Constructivist Learning Theory, the Affective Filter Hypothesis, and Self-Determination Theory. The findings reveal that students experienced SCDC as meaningful, empowering, and transformative, as it allowed personal expression and greater control over learning. While students confronted linguistic, technical, and psychological challenges, these difficulties became opportunities for constructive practice, reflection, and development. This study also shows multidimensional growth, categorized into linguistic, digital, motivational, and identity development. Overall, this study concludes that SCDC functions not only as a speaking task but also as a holistic learning pathway that connects experiences, challenges and growth into a transformative learning process. Finally, this study provides significant implications for language teaching and learning.